Biochemical characterization and evaluation of virulence of a fructosyltransferase-deficient mutant of Streptococcus mutans V403. - Schroeder, V A (1989)
The Streptococcus mutans extracellular fructosyltransferase (FTF) enzyme may play a role in the formation of dental caries by synthesizing a fructan polymer that serves as an extracellular storage polysaccharide. We sought to determine if an FTF-deficient strain of S. mutans was less virulent than wild-type cells in a rat animal model system. Cloned ftf gene sequences from S. mutans GS5 were used to generate a defective copy of the ftf gene by inserting into the ftf coding region a DNA fragment which encoded erythromycin resistance. The plasmid which carried the defective ftf construct was introduced into S. mutans V403 by using genetic transformation. This defective construct replaced, by allelic exchange, the wild-type copy of the ftf gene carried on the V403 chromosome. FTF activity assays indicated that the recombinant strain, V1741, was deficient in fructan synthesis. However, extracellular protein preparations from this strain displayed an increased ability to generate glucose polymers (glucans) compared with V403 preparations. Levels of adherence to glass and rat tooth surfaces by strain V1741 were similar to those of the V403 strain. Both strains caused moderate decay on rat tooth surfaces; however, the FTF-deficient strain was less pathogenic compared with the wild-type strain. These results suggest that FTF activity contributes to the pathogenicity of S. mutans V403, possibly by generating extracellular fructans which serve as storage compounds.